Emergency remote education during COVID-19. Experience of principals in elementary schools in Aguascalientes - Razo Ruvalcaba, Alma Cristina; Ruiz Cuéllar, Guadalupe (IE Revista de Investigación Educativa de la REDIECH, 2023)
Abstract This article comes from a qualitative research with a phenomenological approach whose objective was to characterize the experience lived by principals of public elementary schools during the period of emergency remote education (ERE) due to COVID-19 in Aguascalientes. The results present the experiences of three Principals of schools located in communities with similar socioeconomic level. The outcomes show that the beginning of the ERE was in the framework of uncertainty and the improvisation of strategies, while teachers and Principals were trained in various technological platforms. For this reason, the Principals got closer to the educational community because they tried to hold support focused on constant and active communication to know the needs and concerns of each of its members to support them, despite the inexperience in emergency scenarios and the lack of resources provided by the State educational authorities.